Design of 200 MHz CW He2+ APF-DTLs for 211At production - LiangZhou Yao; CanYu Wang; ZhengMao Zhang; Wei Ma; Liping Zou; Zhen Yang; Jinghe Yang; Liang Lu (Nuclear Engineering and Technology, 2025)
Targeted Alpha-particle Therapy (TAT) has become a significant therapeutic way for cancer, as it can reduce relapsed refractory cancer. 211At is one of the most promising alpha-emitting radionuclides. To boost its production and facilitate applications, we designed 200 MHz drift tube linacs (DTL) operating in continuous wave (CW) mode, which accelerates a 3 mA He2+ beam from 6.4 MeV to 28 MeV for 211At production. Using the alternative phase focusing (APF) beam dynamics to get a compact structure. To ensure high acceleration efficiency, we limit the total cavity length to 2.5 m. The cavity design maintains the gap voltage distribution in close alignment with the beam dynamics, with a maximum deviation of under 1 %. The design achieves 99.98 % beam transmission efficiency. The cavity employs an interdigital H-mode (IH) structure, achieving an unloaded quality factor of 13,635 and a Kilpatrick (Kp) factor of 1.59 in DTL-1, while DTL-2 reaches 14,894 and 1.53 respectively. To ensure stable CW operation, the cooling system has been designed to effectively manage the thermal load during operation, ensuring the system remains within safe limits. This paper presents the detailed design and results of the nuclear medicine linac, including beam dynamics, RF design, and cooling system analysis.